MENINGKATKAN KETERAMPILAN PROSES SAINS DAN HASIL BELAJAR SISWA PADA MATERI KOLOID DENGAN MODEL INKUIRI TERBIMBING (GUIDED INQUIRY) PADA SISWA KELAS XI IPA 1 SMA NEGERI 11 BANJARMASIN - Mika Ariani; Abdul Hamid; Leny Leny (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2015)
Abstract. This study is aimed to determine the improvement of students' process skills, student learning outcomes, teacher activities, student activities and student responses to the application of guided inquiry learning model. This study applies classroom action research design by using 2 cycles. Each cycle consists of planning, action, observation and evaluation, as well as analysis and reflection. The subject of this study was students of class XI IPA 1 SMAN 11 Banjarmasin. There were two instruments used in this study: 20 questions of process skills and learning outcome test by using objective question type and non test instrument. The results of this study showed that (1) An increase in the skills of students at 23.86% (2) An increase in student learning outcomes was 11.7% (3) An increase in the activity of the criteria of good teachers in the first cycle to the criteria very well in the second cycle (4) An increase in the activity of students of both criteria in the first cycle to the criteria very well in the second cycle (5) the student showed a positive response to the application of guided inquiry learning model.Keyword : science process skills, student learning outcome, Guided Inquiry